Encapsulation of Lactic acid bacteria in calcium alginate beads for higher bacteriocin production - Khandare SS; Patil SD (International Journal of Life Sciences, 2017)
Lactic acid bacteria (LAB) strains LAB -A, LAB -B and LAB-C isolated from batter of idli, very popular fermented food of south India and identified to species level using 16 S rRNA sequencing as Pediococcus acidilactici CSI29MX, Pediococcus parvulus MF 233 and Pediococcus pentosaceus QN1D respectively. All the three strains produced bacteriocins that inhibited Gram positive food borne pathogen Staphylococcus aureus and Gram negative Pseudomonas aeruginosa. LAB strains were encapsulated in calcium alginate for possible higher bacteriocin production. After 72 h encapsulated LAB demonstrated remarkable increase in bacteriocin production with 2600 and 2800AU/ml tested against S.aureus and P.aeruginosa respectively and viable cell number of encapsulated LAB increased from 4.5 x106 to 6.3 x106/ml during 24 to 72 h as compared to free cells with 1100 AU/ml and 1000AU/ml, against S.aureus and P.aeruginosa respectively and decreased remarkably with free cells from 4.2 x106 to 1.2 x106/ml after 24 h. Encapsulated L. acidophilus MTCC 10307 , standard strain exhibited 2000 AU/ml and 2200 AU/ml compared to free cells with 1100 and 900 AU/ml. The isolates Pediococcus acidilactici CSI29MX, Pediococcus parvulus MF 233 and Pediococcus pentosaceus QN1D showed higher potential for bacteriocin production than L. acidophilus MTCC 10307.